Design and construction of a control and tracking system based on servomotors to optimize the angle of incidence of solar radiation - Bravo Pachas, Daniel Antonio (2022)
The research project consists of the design and construction of a prototype of a two-axis solar tracking system, which is based on automation using Arduino IDE programming software with photoresistors for positioning the photovoltaic module, in order to optimize the capture of solar radiation. The result of the development of the experimental test has allowed concluding that the greatest power generation has been achieved by using an ACS712 sensor, achieving measurements of greater solar radiation between 10:00 a. m. and 5:00 p. m. of the day. Likewise, between 11:45 a. m. and 1:00 p. m. a current is produced that oscillates between 0,60 A and 0,62 A, achieving optimal performance and with the fixed position system 0,60 A is reached at 10:45 a. m. and it remains constant between 0,60 A and 0,62 A until 1:45 p. m. The average power obtained for the panel in a fixed position is 5,37 watts for 7 hours, while when applying the solar tracking system 6,1 watts were reached, producing an increase of 13,67 %.